Generation of an induced pluripotent stem cell line (TRNDi003-A) from a Noonan syndrome with multiple lentigines (NSML) patient carrying a p.Q510P mutation in the PTPN11 gene - Li, Rong (Stem Cell Res, 2018)
Noonan syndrome with multiple lentigines (NSML), formerly known as LEOPARD Syndrome, is a rare autosomal dominant disorder. Approximately 90% of NSML cases are caused by missense mutations in the PTPN11 gene which encodes the protein tyrosine phosphatase SHP2. A human induced pluripotent stem cell (iPSC) line was generated using peripheral blood mononuclear cells (PBMCs) from a patient with NSML that carries a gene mutation of p.Q510P on the PTPN11 gene using non-integrating Sendai virus technique. This iPSC line offers a useful resource to study the disease pathophysiology and a cell-based model for drug development to treat NSML.